Intraoperative local infiltration with ropivacaine 0.5% in women undergoing vaginal hysterectomy and pelvic floor repair: Randomized double-blind placebo-controlled trial. (May 2019) - Athanasiou, Stavros; Hadzillia, Sophia; Pitsouni, Eleni; Kastanias, Stamatios; Douskos, Athanasios; Valsamidis, Dimitris; Loutradis, Dimitris; Grigoriadis, Themos
Abstract: Objective: To evaluate the effectiveness of infiltration with ropivacaine 0.5% on controlling postoperative pain in women undergoing vaginal hysterectomy (VH) and pelvic floor repair for prolapse stage > II. Study design: This double-blind randomized 1:1 placebo-controlled trial included 59 women. Thirty millilitres of ropivacaine 0.5% or placebo was infiltrated in the round and uterosacral ligaments and in the perineal body. Primary outcomes included postoperative pain intensity at rest and during cough (measured using 10-cm visual analogue scale), and proportion of patients reporting moderate/severe pain. Secondary outcomes included morphine consumption and assessment of nausea, vomiting and sedation. Outcomes were compared between groups at 2, 4, 8 and 24 h postoperatively. Statistical ( p -values) and clinical significance effect size [Cliff's delta] [95% confidence interval (CI)] and odds ratio (95% CI) of results were assessed. Outcomes are presented as median (min–max) and n (%). Results: Pain intensity was lower after ropivacaine infiltration compared with placebo at 2 and 4 h postoperatively at rest [0.5 (0.1–7.2) vs 1.1 (0.2–9.3) ( p = 0.007) and 1.3 (0.1–5.1) vs 3.1 (0.1–9.8) ( p = 0.02), respectively] and during cough [0.9 (0.1–8.9) vs 1.9 (0.1–10) ( p = 0.03) and 1.6 (0.1–4.7) vs 3.2 (0.3–9.6) ( p = 0.009), respectively]. The proportion of patients with moderate/severe pain was significantly less after ropivacaine infiltration compared with placebo at 2, 4 and 8 h postoperatively at rest [4% vs 32% ( p = 0.03), 16% vs 44% ( p = 0.03) and 12% vs 40% ( p = 0.02), respectively] and during cough [8% vs 40% ( p = 0.008), 16% vs 52% ( p = 0.007) and 20% vs 52% ( p = 0.02), respectively]. Patients in the ropivacaine group consumed significantly less morphine compared with those in the placebo group up to 24 h postoperatively [4 (0–17) mg vs 7 (0–19) mg ( p = 0.02)]. The incidence of nausea and vomiting was 3 (12%) and 0–2 (0–8%) in the ropivacaine group, compared with 1–7 (4–28%) and 1–4 (4–16%) in the placebo group. No significant difference was found in the proportion of patients using morphine, proportion of patients reporting the presence of nausea/vomiting, and the intensity of sedation between the groups (all p > 0.05). Conclusion: Local infiltration with ropivacaine 0.5% significantly reduces postoperative pain and morphine consumption in patients undergoing VH and pelvic floor repair for advanced pelvic organ prolapse.